The Usefulness of Interactive Governance for Underground Planning. Issue 2 (1st June 2019) - Nouzari, Ehsan; Hartmann, Thomas; Spit, Tejo
Abstract : The underground provides many spatial planning opportunities as it offers space for structures, but also functions as a resource for energy. To guide developments and use the capabilities the underground provides, the Dutch national government started a policy process for the Structuurvisie Ondergrond (a master plan). Stakeholders are involved in the policy process because of the many interests linked to underground functions. However, past policy processes related to the underground dealt with lack of stakeholder satisfaction. This article explores a quantitative approach by focusing on (a) statistical testing of four criteria of interactive governance and (b) using said criteria to evaluate the satisfaction of stakeholders in a policy process. This article highlights the usefulness of a more quantitative approach and provides new insights into the relation between interactive governance and the procedural satisfaction of stakeholders. It also provides insights that help to improve interactive governance in terms of process management to achieve greater procedural satisfaction.